Evaluación de nuevas estrategias tecnológicas para la optimización terapéutica en pacientes con deficiencia de coenzima Q10 - Ehrenhaus Masotta, Natalia (2022)
In the last years the recommended Coenzyme Q10 (CoQ10) therapeutic dose has significantly increased, reaching values as high as 50 mg/kg/day. The aim of this work was to develop a new, stable, safe and bioavailable high-dose CoQ10 form, satisfying the high CoQ10 requirements of adult patients, and promoting the adherence to the treatment.\nDifferent types of edible formulations were evaluated, of which the oleogels containing medium chain triglycerides oil, ethylcellulose and sorbitan monostearate proved to be the best matrix to vehiculize 1 g CoQ10/disk, which remained stable at 25°C for 18 months. The developed oleogel disk had a final mass of 5 g and offered a comfortable and rapid disintegration in the oral cavity, thus promoting the adherence to the treatment. The toxicity results suggested that the oleogel was safe. Single- and repeated dose supplementation assays were performed on adult volunteers and both showed that the CoQ10 loaded in the oleogel became bioavaliable. An increase in plasmatic vitamin C and calcio levels were also observed, and vitamin C positively correlated with the higher CoQ10 plasmatic concentrations. This study allows us considering the oleogel as a potential alternative to satisfy the high-dose CoQ10 therapeutic demands.